Assessing and enhancing migration of human myogenic progenitors using directed iPS cell differentiation and advanced tissue modelling. Issue 10 (26th September 2022) - Choi, SungWoo; Ferrari, Giulia; Moyle, Louise A; Mackinlay, Kirsty; Naouar, Naira; Jalal, Salma; Benedetti, Sara; Wells, Christine; Muntoni, Francesco; Tedesco, Francesco Saverio
Abstract: Muscle satellite stem cells (MuSCs) are responsible for skeletal muscle growth and regeneration. Despite their differentiation potential, human MuSCs have limited in vitro expansion and in vivo migration capacity, limiting their use in cell therapies for diseases affecting multiple skeletal muscles. Several protocols have been developed to derive MuSC‐like progenitors from human induced pluripotent stem (iPS) cells (hiPSCs) to establish a source of myogenic cells with controllable proliferation and differentiation. However, current hiPSC myogenic derivatives also suffer from limitations of cell migration, ultimately delaying their clinical translation. Here we use a multi‐disciplinary approach including bioinformatics and tissue engineering to show that DLL4 and PDGF‐BB improve migration of hiPSC‐derived myogenic progenitors. Transcriptomic analyses demonstrate that this property is conserved across species and multiple hiPSC lines, consistent with results from single cell motility profiling. Treated cells showed enhanced trans‐endothelial migration in transwell assays. Finally, increased motility was detected in a novel humanised assay to study cell migration using 3D artificial muscles, harnessing advanced tissue modelling to move hiPSCs closer to future muscle gene and cell therapies. Synopsis: This study describes an advanced framework to assess, model and enhance migration of human skeletal myogenic progenitor cells using platforms including induced pluripotent stem (iPS) cells, RNAseq, single cell profiling and tissue engineering. Activation of NOTCH and platelet‐derived growth factor (PDGF) signalling pathways induces conserved transcriptional changes in mouse and human tissue‐ and iPS cell‐derived myogenic progenitors (hiMPs). Combined activation of NOTCH and PDGF signalling via Delta‐like 4 (DLL4) and PDGF‐BB treatment assessed via single cell migratory profiling results in enhanced motility of hiMPs. Organ‐on‐chip and transwell assays show increased trans‐endothelial migration of treated hiMPs not mediated by enhanced adhesion. A novel 3D assay modelling intramuscular migration using engineered muscles shows increased motility of treated hiMPs in a biomimetic environment. Abstract : This study describes an advanced framework to assess, model and enhance migration of human skeletal myogenic progenitor cells using platforms including induced pluripotent stem (iPS) cells, RNAseq, single cell profiling and tissue engineering.